Study on Total Antioxidant Status in Relation to Oxidative Stress in Type 2 Diabetes Mellitus - Rani, A. Jamuna (JCDR Research and Publications (P) Limited, 2014)
Background: Diabetes Mellitus is a condition of increased oxidative stress and requiries antioxidants. The sum of endogenous and food derived antioxidants represents the total antioxidant activity of the system. The cooperation among different antioxidants provides greater protection against damage caused by reactive oxygen species or reactive nitrogen species, than any single compound alone. Thus the overall antioxidant capacity may provide more relevant biological information compared to that obtained by the measurement of individual components, as it considers the cumulative effect of all antioxidants present in plasma and body fluids and hence the study. Materials and Methods: The study population included healthy volunteers from staff of Sree Balaji Medical College & Hospital (SBMC&H) and Type 2 Diabetic patients attending SBMC&H, Chennai, India. Malondialdehyde levels and total antioxidant status of the case and controls was assessed. Results: A significant decrease in the total antioxidant status among Diabetic patients and significant increase in their malondialdehyde levels in comparison to healthy controls was observed. Conclusion: Type 2 Diabetes Mellitus is a condition in which there is increased oxidative stress as evident by increased Malondialdehyde levels and the condition calls for utilization of antioxidants to combat the oxidants thereby resulting in decreased total antioxidants status.